Depression, Anxiety and Quality of Life in Patients with Chronic Hepatitis C Virus Infection in Vojvodina - Dragana Kačavenda-Babović; Predrag Đurić; Radomir Babović; Milotka Fabri; Maja Ružić; Vojislava Bugarski Ignjatović (Acta Clinica Croatica, 2021)
The objective of this study was to investigate the prevalence of depression and anxiety among patients with chronic hepatitis C and how depression and anxiety correlate with respective health-related quality of life (HRQoL) domains, sociodemographic factors, and clinico-epidemiological characteristics. This prospective study involved 150 patients with chronic hepatitis C awaiting interferon treatment for hepatitis C and 150 healthy subjects. All individuals enrolled in the study completed the Short Form 36 (SF-36) questionnaire and Hospital Anxiety Depression Scale. The symptoms showed greater severity/score among patients with chronic hepatitis C for both depression (t=3.37; p<0.01) and anxiety (t=2.35; p<0.05). Regression analysis was used for estimating the relationship between depression and the set of predictors (domains of the SF-36 questionnaire). Three HRQoL domains (Physical Functioning, Vitality, and Mental Health) were found to have the strongest predictive contribution to the occurrence of depression. A series of Kruskal-Wallis and Mann- Whitney tests showed a significant difference in depression level between marital status categories (χ2(2)=7.86, p<0.05). Divorced participants had significantly higher scores compared to married participants (Z=-2.40, p<0.05) and single participants (Z=-2.75, p<0.01). Unemployment was associated with a higher degree of depression and anxiety. There was no association identified between duration of the disease, route of hepatitis C virus transmission, existence of cirrhosis, and depression or anxiety. The findings of this study can assist in developing a standard protocol for the management of chronic hepatitis C that will include psychological assessment and support.